Pengaruh Kompensasi dan Kepuasan Kerja terhadap Komitmen Organisasional Perawat dan Bidan Kontrak di RS Bhayangkara Hasta Brata Batu Malang - Prabowo, Akhmadi; Alamsyah, Arief; Noermijati, Noermijati (Jurnal Aplikasi Manajemen, 2016)
This study aims to determine the effect of compensation and job satisfaction ofnurses and midwives to organizational commitment in Hasta Brata Bhayangkara Hospital Batu Malang. This study uses a quantitative approach using descriptive analytic survey with cross sectional study, with 37 respondents contract nurses and midwives in the Bhayangkara Hospital Hasta Brata Batu. The research instrument uses PSQ (Pay Satisfaction Questionnaire) on variable compensation, MSQ (Minnesota Satisfaction Questionare) on job satisfaction variables, and OCS (Organizational Commitment Scale) on the variable organizational commitment. Data analysis is using path analysis. The results show that compensation has siqnifikan effet either directly or indirectly through job satisfaction on organizational commitment of nurses and midwives in hospitals Bhayangkara Hasta Brata Batu Malang.